PROBLEMS AND REFORM STRATEGIES OF COLLEGE DANCE EDUCATION UNDER THE BACKGROUND OF QUALITY EDUCATION - yao, lei (Pacific International Journal, 2024)
College dance education plays a crucial role in training qualified dance professionals and promoting the art form. However, it currently faces problems affecting program quality, including lack of standardization, outdated curricula and facilities, shortages of qualified faculty, and more. This paper analyzes key issues and challenges for college dance programs in China through an extensive literature review. Potential reform measures are proposed such as improving teacher training, modernizing curricula and teaching methods, upgrading facilities and equipment, and strengthening industry partnerships. Findings suggest comprehensive reforms are needed across areas such as administration, curriculum, faculty, facilities and assessment to improve program quality and enable college dance education to better meet the needs of the cultural market.